Ethno Parenting: Early Childhood Character Development Based on Local Wisdom of the Sasak Tribe - Erda Sunifa Asri; Hidayatussoalihah Hidayatussoalihah; Mertina Mertina; Halimatussakdiah Halimatussakdiah; Baiq Nunike Sulvia Dewi; Lalu Sumardi (Lafadz Jaya Publisher, 2024)
This study aims to describe how the character development model for early childhood is based on local wisdom in the Sasak Tribe. This study was conducted with a focus on local Sasak wisdom that is relevant to the development of early childhood character and ethno parenting practices in the Sasak tribe community. The type of research used is qualitative research. The subjects of the study were the traditional chiefs of the Ende Sasak tribe, the Bayan Sasak tribe and the local community in the Sasak tribe. Data collection was carried out using observation, interview and documentation methods. Data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the local wisdom of the Sasak Tribe has several character value developments in children consisting of religious values, mutual cooperation values, discipline and responsibility values, preservation of art and culture and life values.